2014
DOI: 10.1590/s1413-35552012005000144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of properties of the Vestibular Disorders Activities of Daily Living Scale (Brazilian version) in an elderly population

Abstract: Background The Vestibular Disorders Activities of Daily Living Scale (VADL) is considered an important subjective assessment to evaluate patients suffering from dizziness and imbalance. Although frequently used, its metric characteristics still require further investigation. Objective This paper aims to analyze the psychometric properties of the Brazilian version of the VADL in an elderly population.Method The sample comprises patients (≥65 years old) with chronic dizziness resulting from vestibular disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…40 Nowadays, Cawthorne-Cooksey vestibular training is considered the gold standard protocol within this framework. 31 41 Although further research is needed, conventional vestibular training has been reported as superior to no intervention and at least as effective as exercise-based approach (Frenkel exercises and endurance training) for improving dizziness, balance and fatigue in any MS type. 38 39 Currently, there is an exponential growth of studies that evaluate the effectiveness of virtual reality (VR) applied to vestibular rehabilitation in other diseases.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…40 Nowadays, Cawthorne-Cooksey vestibular training is considered the gold standard protocol within this framework. 31 41 Although further research is needed, conventional vestibular training has been reported as superior to no intervention and at least as effective as exercise-based approach (Frenkel exercises and endurance training) for improving dizziness, balance and fatigue in any MS type. 38 39 Currently, there is an exponential growth of studies that evaluate the effectiveness of virtual reality (VR) applied to vestibular rehabilitation in other diseases.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Thus, less than half the 25 questions of DHI reflect activity limitations or participation restriction in patients with vestibular disorder. In another activity scale, the Vestibular Disorders Activities of Daily Living Scale (VADL), a plateau in the DHI score was achieved while the VADL score continued to increase, indicating that the DHI scale weakly correlates with VADL [ 21 ]. It is important to highlight that such discrepancy exists because of different dimensions evaluated by different scales.…”
Section: Discussionmentioning
confidence: 99%
“…Then, with the assistance of an occupational therapy student and certified driving rehabilitation specialist, Jennifer Wells, our investigator did a study of driving problems in people with vestibular disorders (Cohen, Wells, Kimball, & Owsley, 2003). That initial work also led to the development and norming of a better ADL scale, the Vestibular Disorders Activities of Daily Living Scale (VADL), with assistance from an occupational therapy student, Angela S. Adams Cohen, Kimball, & Adams, 2000), and a paper refining that scale with a Brazilian physical therapist, Natalia A. Ricci, as part of her doctoral research (Ricci, Aratani, Caovilla, Cohen, & Ganança, 2014). The VADL has become widely used and has contributed to acceptance of the idea that patients with vestibular impairments have functional limitations.…”
Section: Having a Research Careermentioning
confidence: 99%